STATIC OPTIMISATION OF MECHANICAL SYSTEMS BASED ON THE METHOD OF EXTREMAL REGULATION - Jaroslav (Scientific Journal of Silesian University of Technology. Series Transport)
A change in torsional stiffness of pneumatic tuners can be achieved by changing the pressure of the gaseous medium in the course of the mechanical systems' operation or while idle. Based on this statement, we tuned mechanical systems with torsional vibration when they are either idle or when they reach stable condition during operation. The principle of tuning mechanical systems with torsional vibration during operation when their condition is stable lies in the appropriate adaptation of basic dynamic properties (dynamic torsional stiffness and damping factor) of the pneumatic tuner to the dynamics of the system. This was achieved with a control system that helps create a closed control feedback loop. In this way, we can continuously change, that is, adapt the dynamic properties of the pneumatic tuner to the dynamics of the mechanical system so that no dangerous torsional vibrations occur while the system is in operation mode.